Criteria for Occupational Health Prevention for Solar UVR Exposed Outdoor Workers-Prevalence, Affected Parties, and Occupational Disease - Wittlich, Marc (Frontiers in Public Health, 2022)
Non-melanoma skin cancer (NMSC) is the most common cancer in Western countries. Legislative bodies and stakeholders like WHO and EU strongly promote protection against solar UVR, especially in workers. Occupational health prevention must be introduced as a strong instrument in workers protection also with regard to occupational disease issues. To date, criteria for both occupational health prevention and occupational disease are missing and the identification of risk groups has no metric basis. Here I report a criteria analysis based on the largest comprehensive data set of occupational ultraviolet radiation exposure of outdoor workers. With detailed research on occupation-specific dosimetric measurements of 45.000 measurement days in 176 occupations and sub-occupations, it is possible to map criteria for occupational health prevention specifically and to identify affected occupations. The number of employees affected can be elucidated worldwide. For the first time, a direct link to retrospective occupational disease criteria could be established. Of the 176 occupations and sub-occupations selected for this work, 153 (= 87%) exceed the criterion for occupational health prevention and thus need special attention. This includes all occupations with annual exposures of more than 150 SED. Employment figures for the EU and the world yield the total number of affected workers to be 36.1 million and more than 500 million, respectively. These new criteria for occupational health prevention are valid and in good agreement with international researchon limit values by WHO and ICNIRP. If applied correctly and consistently, these criteria can prevent occupational disease. It will be possible to identify occupations and sub-occupations that have an urgent need for prevention to avoid chronic skin damage leading to cancer. This resarch serves as a basis for policy making and clinical risk identification, as well as for daily practice of occupational physicians and employers responsible for risk assesment.